Interferon gamma‐mediated prevention of tumor progression in a mouse model of multiple myeloma - Zoltán Kellermayer; Sabrin Tahri; Madelon M. E. deJong; Natalie Papazian; Cathelijne Fokkema; Elodie C. G. Stoetman; Remco Hoogenboezem; Gregory vanBeek; Mathijs A. Sanders; Louis Boon; Chelsea Den Hollander; Annemiek Broijl; et al. (HemaSphere)
Abstract Malignant plasma cells in multiple myeloma patients reside in the bone marrow and continuously interact with local immune cells. Progression and therapy response are influenced by this immune environment, highlighting the need for a detailed understanding of endogenous immune responses to malignant plasma cells. Here we used the 5TGM1 murine transfer model of multiple myeloma to dissect early immune responses to myeloma cells. We modeled stable and progressive disease by transferring 5TGM1 murine myeloma cells into C57Bl/6 mice and KaLwRij mice, respectively. We used flow cytometry and single‐cell and bulk transcriptomic analyses to characterize differential immune responses in stable and progressive disease. Transfer of 5TGM1 cells in C57Bl/6 mice led to stable disease with low tumor burden in a subset of animals. Stable disease was associated with sustained activation and expansion of NK cells, ILC1, and CD8+ T cells, a response that was lost upon disease progression. Single‐cell RNA‐sequencing of immune cells and bulk RNA sequencing of immune and mesenchymal stromal cells implicated the activation of interferon responses as a central immune pathway during stable disease. Experimentally, neutralization of IFNγ significantly increased myeloma development and progression in C57Bl/6 mice, testifying to the importance of this pathway in early disease control. In conclusion, we provide a framework for studying immune responses to multiple myeloma progression in immunocompetent and genetically modifiable mice and highlight the importance of bone marrow immunity in tumor control.